Removing Corn Stover Has Little Effect on Soybean Performance in a Corn–Soybean Rotation. Issue 1 (1st December 2013) - Nelson, Kellar E.; Boardman‐Smith, Deanna S.; Wiebold, William J.
Abstract : Corn ( Zea mays ) stover is an attractive choice for cellulosic ethanol production because it is readily available and easily obtainable. Understanding how corn stover removal affects soybean ( Glycine max ) emergence and yield is essential to developing appropriate management recommendations for both crops in a corn–soybean rotation. The objectives of this study were to determine (i) the effects of corn stover removal on soybean emergence and yield and (ii) if cover crops ameliorate any of the possible negative effects to soybean from corn stover removal. Removing stover allowed soil temperature to increase, slightly, but cover crops had little or no effect. Stover removal and cover crops had no effect on three soybean emergence parameters except stover removal resulted in a more nearly uniform stand in 1 yr. Soybean stand density increased with stover removal. Soybean grain yield was not affected by either stover removal or the use of cover crops. Removing corn stover may have long term effects on important soil characteristics and these may impact future grain‐crop productivity.